First report of molecular detection of Carnivore bocaparvovirus 1 (former CnMV: Canine Minute Virus) in Chilean domestic dogs - González-Hein, G.; Huaracán, B.; Aguirre, I. (Austral Journal of Veterinary Sciences, 2020)
Carnivore bocaparvovirus 1 (CnMV) infects dogs worldwide and can be responsible for different clinical signs in neonates and bitches during gestation. There is a limited number of CnMV sequences available in the NCBI database, so far. The present preliminary study aimed to obtain evidence of CnMV infection status among domestic dogs in Chile and evaluate the genetic relatedness of the sequences obtained with any type of bocaparvovirus already reported. Two partial nucleotide sequences of the VP2 coding gene were obtained from forty blood samples and compared with 23 available sequences of Carnivore bocaparvovirus from 1 to 6. Chilean sequences grouped within Carnivore bocaparvovirus 1 group, being sequence 5434 (Accession number, MH544475) more similar to the Japanese strain HM-6 and sequence 5423 (Accession number, MH544476) to the Chinese strain SH1.